Feasibility study of fast ion loss diagnostics for CFQS by beam ion loss calculation on vacuum vessel. (27th September 2021) - Ogawa, K.; Isobe, M.; Seki, R.; Nuga, H.; Yamaguchi, H.; Sangaroon, S.; Shimizu, A.; Okamura, S.; Takahashi, H.; Oishi, T.; Kinoshita, S.; Murase, T.; et al.
Abstract: A feasibility study for installing fast-ion loss diagnostics (FILDs) is initiated to understand energetic ion loss process in a quasi-axisymmetric stellarator CFQS. The calculations of beam ion orbit, the guiding center orbit code including the slowing down by bulk plasma in the Boozer coordinates and the collisionless Lorentz orbit code in the Cartesian coordinates, are performed to estimate the toroidal/poloidal distribution of beam ion losses on a vacuum vessel. We observed that loss points on the vacuum vessel are mainly located at the upper side of torus according to gradient magnetic field drift direction. Based on the loss distribution on the vacuum vessel, a possible location of FILD for CFQS is investigated. Although the energy of lost beam ions is ∼10 keV, relatively high-energy (> 20 keV) components can be measured on the upper side of the torus in the low-density case. Furthermore, the radial or vertical dependence of beam ion loss flux at candidate movable scintillator-type FILD positions is obtained. A considerable number of particles reach the scintillator-type FILD position. The energy and pitch angle distribution of beam ions reaching the FILD position shows that scintillator-type FILDs can measure co-going transit beam ions with energy of ∼25 keV and pitch angle of ∼140 degrees and transition beam ions with energy of 10–15 keV and pitch angle of ∼80–100 degrees.